2021
DOI: 10.3390/s21134571
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework for Quantifying Accuracy and Precision of Event Detection Algorithms in FES-Cycling

Abstract: Functional electrical stimulation (FES) is a technique used in rehabilitation, allowing the recreation or facilitation of a movement or function, by electrically inducing the activation of targeted muscles. FES during cycling often uses activation patterns which are based on the crank angle of the pedals. Dynamic changes in their underlying predefined geometrical models (e.g., change in seating position) can lead to desynchronised contractions. Adaptive algorithms with a real-time interpretation of anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…If other volunteers had participated in the experiment, the mechanical adjustments would have to be carried out individually, which would have demanded a relative effort to define the best FES pulse parametrization (i.e., the stimulation range of each angle). Studies have suggested the use of IMUs as a better approach for cycling phase detection, which could reduce this effort and improve FE -pedaling by SCI individuals [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…If other volunteers had participated in the experiment, the mechanical adjustments would have to be carried out individually, which would have demanded a relative effort to define the best FES pulse parametrization (i.e., the stimulation range of each angle). Studies have suggested the use of IMUs as a better approach for cycling phase detection, which could reduce this effort and improve FE -pedaling by SCI individuals [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In order to derive a stimulation pattern, several procedures could be considered. One could, for instance, detect the maximal force and then set the start angle at the first zero transition before the maximum and the stop angle at the first zero transition after the maximum [ 14 ]. Such a range would likely maximize the power output, but also the muscular fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in FES cyclists, which include individuals with various types of motor disabilities, has created a growing need for assessment tools in order to determine the most efficient electrical stimulation strategies to adapt to the different needs, such as optimizing the stimulation patterns (the timing in which the cyclist’s leg muscles are activated) in order to achieve a smooth and powerful cycling movement. Furthermore, selecting the stimulation parameters, such as electrical pulse shape and charge density, that will maximize the torque generated by the muscle contraction while minimizing the subsequent muscular fatigue will have a major influence over the cycling efficiency and its potential health benefits [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…knee-extension, knee-flexion) during cycling. Previously, research groups have investigated the use of inertial measurement units (IMUs) to control stimulation in FES-Cycling, by assessing the thigh [ 13 , 14 ] or knee angle [ 15 , 16 ]. The motivation for this was to create a simpler definition of stimulation intervals, which automatically adapts for certain variations during cycling (e.g.…”
Section: Introductionmentioning
confidence: 99%